OLD AND LONELY: THE LONELINESS NARRATIVE, MORAL REGULATION AND THE MEDIA - Sullivan, M P (Innov Aging, 2018)
Media campaigns in the United Kingdom portray loneliness as a major social and public health issue. The aim of this study was to explore loneliness representations in the media in England and their possible relationship with key policy initiatives for an ageing population. Using a purposive sampling technique, we adopted a qualitative content analysis of print and digital media targeted at loneliness and older people over a 10 year period. Our findings suggest that skilled marketing within the media has depicted loneliness as an expected consequence of older age, a high burden of ‘disease’ for the health care sector and easily amenable to social intervention. This highly stigmatizing discourse also continues to reinforce the burden of an ageing population. We conclude that there is a need for a critical analysis of loneliness from the perspective of social and cultural constructions of ageing and the positioning of older people in society.